SEKOLAH BERTARAF INTERNASIONAL - Tawil, Tawil (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
International school (SBI) or internationally Standardized School (ISS), is one of the primary and secondary education innovation in Indonesia, the main pillars for improving the quality, relevance, and competitiveness. Stages that must pass to become SBI is RSBI, SSN or SKM. That is to go to the SBI, the schools are required to pass through the stage into SSN (National Standard School) for elementary and junior high, or SKM (Independent School Category) for high school and vocational school, and then increased to RSBI (international school stubs), and new to the SBI (international school). SBI is basically a SSN plus. SSN is said because the school is still referring to the national standard schools by meeting the eight national education standards (SNP), but should have a plus or international advantages. Since the SBI in addition to using the Indonesian language as the national language and the language of instruction in schools, SBI also require English as the language of instruction in certain subjects, the SBI is also often called the Bilingual Schools Boarding School.Other things that must be met including the use of an international curriculum, international competency, qualification of teachers and international level, mastery of English for students, educators and educational staff at a certain level Toefl, culture and the use of IT (Information Technology ), the development of teaching strategies, use of means of international education, exchange of students with SBI in a foreign country OECD members, management, financing, valuation, and international accreditation. Short said the SBI should qualify the achievement of key employment indicators of a minimum of 8 SNPs, and the achievement of key performance indikatpor additional international standard ISO9000 ISO14000 accredited according to the OECD or other developed countries in education.